Prediction of Liver Volume from Liver Transplant Donor using Biometric Formula compared with Computed Topography Volumetry - Putranto, Agi S; Syafina, Adinda B; Sekarsari, Damayanti; Mazni, Yarman; Moenadjat, Yefta (UI Scholars Hub, 2021)
Introduction. Liver volume calculation is critical in assessing the compatibility and resectability of the graft in living donor liver transplants (LDLT). An accurate estimation of liver volume is a predictor for successful LDLT. The gold standard of liver volume estimation is CT Volumetry. Despite several limitations in the availability of software, facility, and time consumed, there is still disagreement of biometric formula to predict liver volume in Indonesia. Methods: A cross-sectional design study was carried out in Dr. Cipto Mangunkusumo General Hospital, enrolling those who underwent liver transplantation from 1st January 2010 – 3rd October 2019. Bodyweight, body height, body mass index, body surface area, and CT volumetry were the variables of interest in the study and were subjected to analysis. Result. Body weight, body height, and body surface area are found from multivariate analysis in this research. Multivariate logistic regression of body weight with caudal liver volume giving out liver volume estimated equation of estimate liver volume of 479.23 + 13.95 (bodyweight). The equation in this study proposes a biometric formula to estimate liver volume using bodyweight based on Indonesian anthropometry. Conclusion: Bodyweight is proposed for equation formation based on a characteristic patient feature in Indonesia. Accuracy testing of the liver estimation equation discovered in this study proposed an entirely satisfactory result in the Indonesian population